2020
DOI: 10.3390/agronomy10091323
|View full text |Cite
|
Sign up to set email alerts
|

Implications of Abscisic Acid in the Drought Stress Tolerance of Plants

Abstract: Drought is a severe environmental constraint, which significantly affects plant growth, productivity, and quality. Plants have developed specific mechanisms that perceive the stress signals and respond to external environmental changes via different mitigation strategies. Abscisic acid (ABA), being one of the phytohormones, serves as an important signaling mediator for plants’ adaptive response to a variety of environmental stresses. ABA triggers many physiological processes, including bud dormancy, seed germi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 105 publications
(66 citation statements)
references
References 238 publications
3
57
0
Order By: Relevance
“…Metal stress in plants produces excessive amounts of reactive oxygen species (ROS), which lead to oxidative stresses [28,29]. The consequences of oxidative stress involve lipoperoxidation and oxidative damage to membrane lipids, enzymes, chloroplasts, and nucleic acids [28,29]. ROS molecules are extremely reactive, unstable, and toxic at elevated levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Metal stress in plants produces excessive amounts of reactive oxygen species (ROS), which lead to oxidative stresses [28,29]. The consequences of oxidative stress involve lipoperoxidation and oxidative damage to membrane lipids, enzymes, chloroplasts, and nucleic acids [28,29]. ROS molecules are extremely reactive, unstable, and toxic at elevated levels.…”
Section: Discussionmentioning
confidence: 99%
“…Plant metabolic activities generate ROS in small amounts. Under stress conditions, this ROS generation exceeds the maximum level [24,27], leading to oxidative stresses [28,29]. The consequences of oxidative stresses in plants involve lipid peroxidation, electrolyte leakage, and damage to membranes and DNA molecules [24,30,31].…”
Section: Introductionmentioning
confidence: 99%
“…In plants, the signaling network stimulates the defensive system, which triggers the molecular mechanism to respond to specific stress conditions. Calcium ions involved in the transduction of signals under varying stress environments act as a second messenger [151]. Sensitivity to stress signals causes the enrichment of calcium ion level in the cytosol through calcium ion channels, which is recognized by calcium ion-binding proteins that trigger alterations in gene expression as well as plant adaptation to stress conditions [152,153].…”
Section: Molecular Mechanism Of Nanoparticles To Mitigatementioning
confidence: 99%
“…Additionally, Ca is involved in signaling anti-drought responses [32]. Calcium participated in abscisic acid (ABA)-induced drought signal transduction which improved water use efficiency and confer drought tolerance [27,28]. In addition, Ca-sensing proteins have shown to up-regulate drought tolerance signaling events, whereas negative regulation of drought stress is also attributed to these proteins [65].…”
Section: Agronomic Traitsmentioning
confidence: 99%
“…It alleviates the harmful effects of drought on plants by signaling anti-drought responses [26]. Ali et al [27] indicated that the increasing cellular transient Ca participates in the processes abscisic acid (ABA)-induced drought signal transduction. The biosynthesis of ABA has improved water use efficiency and confer drought tolerance in plants [28].…”
Section: Introductionmentioning
confidence: 99%